Reflective Thinking and its Relationship to Decision-Making Among Teachers of Gifted Students in Makkah Al-Mukarramah - Al-Lahyani, Mada Khaled (Journal of Educational and Psychological Sciences, 2024)
The study aimed to identify the degree of reflective thinking among teachers of gifted students in Makkah Al-Mukarramah region, and to identify the degree of decision, and to reveal the existence of a statistically significant correlation between reflective thinking and decision-making. The study population consisted of all teachers of gifted students In the Makkah Al-Mukarramah region, the total number of the sample was (322) , and the number of the final sample was determined (180) female teachers, who were chosen randomly. The following results were reached: Reflective thinking came to a moderate degree among teachers of gifted students, decision-making came to a moderate degree among teachers of gifted students, there were no statistically significant differences in the average degrees of reflective thinking attributed to the variable of experience and academic qualification, and there were no statistically significant differences in the average degrees of decision-making attributed to The variable of experience and educational Qualification.